Crack Pattern Investigation in the Structural Members of a Framed Two-Floor Building due to Excavation-Induced Ground Movement - Mangi, N.; Mangnejo, D. A.; Karira, H.; Kumar, M.; Jhatial, A. A.; Lakhair, F. R. (Engineering, Technology & Applied Science Research, 2019)
Increased urbanization causes traffic and parking issues especially in metropolitan cities like Karachi, London, Shanghai, etc. To accommodate parking issues for the vehicles mainly in urban areas (excavated) underground parking areas under or nearby high rise buildings are preferred. As a result of excavation, ground movements occur that have a major impact on structures, buildings, and utilities. The past research usually oversimplified surface structure as an equivalent elastic beam, which is unable to represent the behavior of a framed building realistically. In this study, the detrimental effects (i.e. crack pattern) on a two-floor RCC framed building founded on piles due to an adjacent excavation-induced ground movement are investigated. Elasto-plastic coupled-consolidation analysis was adopted. The hypoplastic constitutive model was used to capture soil behavior. It is an advanced model which is able to capture the soil unique features which are non-linear behavior, stiffness degradation (with stress, strain & path-dependent), and stress-strain dependent soil dilatancy. The concrete damaged plasticity (CDP) model was used to capture the cracking behavior in the concrete beams, columns and piles. It was revealed that the induced slope and tilting are not equal. Consequently, the frame was distorted. As a result, tension cracks were induced at the inner side of the column.